PEMBERDAYAAN MASYARAKAT MELALUI REMAJA BEBAS NARKOBA - Pitriani; Rizky, Muhammad; Aziza, Prisila; Jamaluddin; Faustine, Ingrid (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
Drugs are an abbreviation of narcotics, psychotropics, and other active ingredients. Another term is NAPZA (Narcotics, psychotropics, and addictive substances). This activity aims to provide counseling or education in the form of socialization and education to adolescents, especially students of MTS Tosale so that they can know the dangers and effects of drug abuse and are expected to help create a younger generation with a more drug-free character. The Drug Socialization activity was implemented on October 26, 2023, at 08.00 and finished at the Tosale Village Office, Banawa Selatan District, Donggala Regency. The method used in this socialization activity is the lecture and documentation method. The results showed that 9 participants participated in the drug socialization activity. It can be concluded that the factors that cause adolescents to abuse drugs are family factors that pay less attention to their children and also environmental factors that can have a big influence. With education and religious education as the outermost wall to prevent drug abuse.